Pengaruh Eksistensi Dewan Komisaris Wanita dan Faktor lainnya terhadap Nilai Perusahaan - Ignacio, Rafael; Lasar, Hilary Flora A T (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Firm value dictates the value of stock price that a company owns thereby, firm value is a crucial thing. The purpose of this study was to obtain empirical evidence regarding the effect of several independent variables on one dependent variable. The dependent variable used in this study is firm value. This study also has independent variables consisting of institutional ownership, managerial ownership, the proportion of independent commissioners, the size of the board of commissioners, the existence of female commissioners, the size of the board of directors, audit committee, profitability, and capital structure. The population used in this study are consumer non cyclicals and consumer cyclicals companies listed on the Indonesia Stock Exchange starting from 2020 to 2022. This population was studied using the purposive sampling method, and got a total of 73 companies that will be used as research samples with a total of 219 data. The results of this study indicate that the proportion of independent commissioners and profitability variable has a positive influence on firm value. On the other hand, the variables of institutional ownership, managerial ownership, the size of the board of commissioners, the existence of a female board of commissioners, the size of the board of directors, audit committee, and capital structure have no effect on firm value.